Deacidification of palm oil using solvent extraction integrated with membrane technology - Lai, S. O. (Penerbit UTM Press, 2016)
In this work, the efficiency of crude palm oil (CPO) deacidification using solvent extraction integrated with membrane technology is studied. Different solvents including ethanol, hexane and methanol were selected to extract the palmitic acid from model fatty system in the model fatty system to solvent ratio of 1:2. Experimental results showed that ethanol was the best solvent to extract palmitic acid from the model fatty system, recording about 65.5% fatty acid reduction in the model fatty system. Three commercial solvent resistant nanofiltration (SRNF) membranes (SolSep NF010206, NF030306, and NF030705) were then selected to examine their respective performance in recovering ethanol from palmitic acid-rich ethanol solvent. The results revealed that the combination of solvent extraction and membrane technology is remarkable simple and waste-free approach to overcome major drawbacks of conventional refinery operation.